Exploring Group A Streptococcus Infections in Infants: A Comprehensive Analysis of Detection, Genotyping, and Antibiotic Resistance Trends in Baghdad: Mengeksplorasi Infeksi Streptokokus Grup A pada Bayi: Analisis Komprehensif tentang Deteksi, Genotipe, dan Tren Resistensi Antibiotik di Baghdad - Mohan, Fatima Rashid (Universitas Muhammadiyah Sidoarjo, 2025)
This study aimed to investigate the prevalence, genetic diversity, and antibiotic resistance of Group A Streptococcus (GAS) infections among pediatric populations in Baghdad, addressing the critical public health challenge posed by rising antibiotic resistance and limited surveillance. GAS infections, caused by Streptococcus pyogenes , range from mild pharyngitis to severe invasive diseases like necrotizing fasciitis. The study analyzed 226 pharyngeal swab samples from children aged 3–14, identifying 21 confirmed GAS isolates. Genotyping revealed significant genetic diversity, with prevalent emm types including emm-1, emm-4, and emm-12, alongside virulence genes such as speB and speA . Household contact with infected individuals significantly increased infection risk (p<0.01), emphasizing transmission dynamics. Antibiotic susceptibility testing highlighted alarming resistance levels, particularly to penicillin (29%) and amoxicillin (6%), contrasting with global trends where penicillin resistance remains low. However, azithromycin (93%) and cefuroxime (90%) demonstrated high efficacy, while macrolide resistance, such as erythromycin (45%), is rising. Linezolid maintained 80% susceptibility, crucial for treating multidrug-resistant infections. Clinical manifestations included fever, respiratory disorders, and hemodynamic instability, consistent with invasive GAS disease. Highlights: GAS prevalent with diverse emm types, virulence genes detected. High resistance to penicillin; azithromycin, cefuroxime effective. Infection risk higher with household exposure; severe symptoms observed. Keywords: Group A Streptococcus, antibiotic resistance, genotyping, pediatric infections, public health interventions